Gesamtausgabe - Maimon, Salomon (frommann-holzboog, 2023)
Deutsche Schriften: Band 1: Aufsätze 1789-1790 -- Band 2: 1791-1792 -- Band 3: 1792-1793 -- Band 4: 1793 -- Band 5: 1794 -- Band 6: 1794-1800 -- Band 7: Briefwechsel (1789-1800)